The Moderating Role of Institutional Quality on the Effect of Household Consumption and Government Expenditure on Economic Growth in Indonesia - Fajar Ardiansyah; Kefvin Melwani; Melly Firdawinata (International Journal of Science and Society, 2026)
The magnitude of household consumption and government expenditure does not guarantee accelerated economic growth without being supported by sound institutional quality, particularly corruption control, which remains a major challenge in Indonesia's governance. This study aims to analyze the moderating role of institutional quality in the effect of household consumption and government expenditure on economic growth in Indonesia. This study employs a quantitative explanatory approach using time series data for the period 2006–2025, obtained from the official World Bank website. The analysis techniques used are multiple regression and Moderated Regression Analysis (MRA). The results show that household consumption (β = 3.489; sig = 0.017) and government expenditure (β = 1.379; sig = 0.015) have a positive and significant effect on economic growth. Institutional quality is able to moderate and strengthen the effect of household consumption (β = 9.100; sig = 0.018) and government expenditure (β = 1.890; sig = 0.013) on economic growth, with an R² of 0.842. These findings confirm that corruption control and improved governance are key to optimizing the effectiveness of fiscal policy and domestic consumption on sustainable economic growth.